The Buzzing "Moo" - Hassan, Mohd Rohaizat; Mansor, Rozaihan; Baba, Mohd Shukri (UPM Press, 2020)
One Health has gained rapid prominence over the past 5 years among the local and international health-related agencies' as a default approach in managing complex human health issues at the local, regional, and global settings. The One Health approach transcends institutional silos, territories, and borders, therefore, requiring an increased aptitude for collaboration and communication alongside fresh perspectives that moves away from the traditional method of problem-solving. This is the second book published by the team from the Malaysia One Health University Network following the successful launch of their first publication. The book presents an additional 10 problem-based cases that are updated to the current disease scenarios and integrated across disciplines and areas. The PBL format allows for active engagement by the students and lets the student take charge of their learning. Adopting student-centered instruction as an approach, the book focuses on skills and practices that enable independent problem-solving and lifelong learning. The cases presented in this book are relevant to Malaysia, Southeast Asia, and can be easily be adapted to other parts of the world. OH-PBL Book 2 is another testament of the commitment and effort by the Malaysia One Health University Network (MyOHUN) members to inculcate one health thinking and spirit in the education of the pre-service workforce from the medical, veterinary, and other relevant disciplines. As a university network, we recognise that training human resources is an arduous task. In addition, ensuring that future workforce skills fit the needs of the country creates an additional layer of challenge to the formulation of training materials. University curricula are not as dynamic as the changing disease landscape, which is why student-centered learning and case-based learning activities are important to transform and enrich students' learning processes, adding dimensions of knowledge that cannot be provided by the usual curricula. The cases from this book can be used to supplement student learning activities or can be used as part of the curriculum to engage students to think beyond the routine and traditional methods. As the coordinator of MyOHUN, I hope you will find these cases useful in teaching your students.